2016
DOI: 10.15585/mmwr.ss6506a1
|View full text |Cite
|
Sign up to set email alerts
|

Youth Risk Behavior SurveillanceUnited States, 2015

Abstract: YRBSS data are used widely to compare the prevalence of health behaviors among subpopulations of students; assess trends in health behaviors over time; monitor progress toward achieving 21 national health objectives for Healthy People 2020 and one of the 26 leading health indicators; provide comparable state and large urban school district data; and help develop and evaluate school and community policies, programs, and practices designed to decrease health-risk behaviors and improve health outcomes among youth. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
718
12
15

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,267 publications
(768 citation statements)
references
References 4 publications
23
718
12
15
Order By: Relevance
“…For example, results from the 2015 cycle of the US Youth Risk Behaviour Surveillance System show lifetime and past-month prevalence rates of cannabis use of 38.6% and 21.7%, respectively. 21 Although a recent report indicated that cannabis use in Ontario decreased over the past 2 decades, from 28.0% in 1999 to 21.3% in 2015, 12 there have been increases in heavy use. For example, the prevalence of daily or near-daily use among adults in the US rose from 1.9% in 2002 to 3.5% in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…For example, results from the 2015 cycle of the US Youth Risk Behaviour Surveillance System show lifetime and past-month prevalence rates of cannabis use of 38.6% and 21.7%, respectively. 21 Although a recent report indicated that cannabis use in Ontario decreased over the past 2 decades, from 28.0% in 1999 to 21.3% in 2015, 12 there have been increases in heavy use. For example, the prevalence of daily or near-daily use among adults in the US rose from 1.9% in 2002 to 3.5% in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…4 Its use is associated with the top 4 leading causes of morbidity and mortality among teens. 5 For YCMC, alcohol use may play a substantial unrecognized role in exacerbating morbidity and increasing health care costs. Although chronic diseases are heterogeneous, YCMC who use alcohol face the potential for negative alcohol interactions (AI) with medications 6 and laboratory tests, treatment adherence, self-care, and underlying disease status.…”
Section: What This Study Addsmentioning
confidence: 99%
“…1 -4 The adverse health consequences of cigarette smoking and marijuana use have been documented, 5,6 with more severe and persistent negative outcomes seen when use is initiated during adolescence and when both substances are used. 1,7,8 Although adolescent cigarette smoking has declined significantly over the past decade, 9 approximately one-third of US adolescents report currently using at least 1 tobacco product, an increase of 35% since 2011. 9 This increase is attributable to the use of alternative nicotinedelivery products, such as electronic cigarettes (e-cigarettes) and hookah.…”
mentioning
confidence: 99%